"I Don't Want You Sitting Next to Me": The Macro, Meso, and Micro of Gaining and Maintaining Access to Government Organizations During Ethnographic Fieldwork. Issue 1 (1st June 2017) - Grant, Aimee
The challenges of access in ethnographic research are well-documented in methodological literature, but poorly described in many empirical studies. To date, very little research has focused on access to organizations. In this article, I describe the ongoing access challenges in a period of fieldwork in UK Jobcentre Plus (welfare) offices. Access was granted in four phases: organizational access at a national level (macro), access to individual offices (meso), access to advisors as interview subjects (very limited micro), and finally access to shadow one welfare advisor (limited micro). However, access to observe multiple advisors (full micro) did not occur. In this article, I draw on field notes and interview extracts from advisors as one source of ethnographic data and compare these to data generated in interviews with benefit claimants who were recruited from charities and interviewed away from Jobcentre Plus offices. Differences were found between these two data sources, which highlight that access arrangements impacted on the data collected. Researchers should acknowledge and reflect upon access arrangements at the macro-, meso-, and microlevel in the presentation of ethnographic research findings.